Bivalve resources of the Chettuva estuary, Kerala - Laxmilatha, P; Velayudhan, T S; Mohamed, K S; Kripa, V; Radhakrishnan, P; Joseph, Mathew; Sharma, Jenny (Indian Journal of Fisheries, 2011)
Clams form a major exploited resource of Chettuva estuary. A rapid survey wascarried out to assess the bivalve resource and potential stock. The estuary harborsan estimated standing stock of 378 t of bivalves; Meretrix casta is the dominantspecies (340 t) followed by Villorita cyprinoides (33.6 t).Â  Aspects of conservationand management of bivalve fishery are detailed. The prospects for enhancingbivalve production from the estuary through relaying/ semi culture of clamsand promoting mussel farming in the lower reaches of the estuary are discussed.